2018
DOI: 10.1007/s00405-018-4898-3
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing evaluation after surgery for obstructive sleep apnea syndrome: uvulopalatopharyngoplasty vs. expansion pharyngoplasty

Abstract: OSAS patients show sub-clinical changes in swallowing pattern before surgery. Both surgical techniques are related to transitory changes in swallowing biomechanics. Complete or partial reversal to pre-operative swallowing parameters occurs 1 month after both surgery techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Other authors have shown that asymptomatic OSA patients might also have altered swallowing patterns before surgery. 16 They investigated 17 OSA patients with objective swallowing videofluoroscopy before and after surgery and found that both UPPP and expansion pharyngoplasty were related to transitory changes in swallowing biomechanics. However, complete or partial reversal to preoperative swallowing parameters occurred already 1 month after both techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have shown that asymptomatic OSA patients might also have altered swallowing patterns before surgery. 16 They investigated 17 OSA patients with objective swallowing videofluoroscopy before and after surgery and found that both UPPP and expansion pharyngoplasty were related to transitory changes in swallowing biomechanics. However, complete or partial reversal to preoperative swallowing parameters occurred already 1 month after both techniques.…”
Section: Discussionmentioning
confidence: 99%
“…UPPP and other previous palatal surgery techniques (e.g., LAUP, UPF) for OSA were based on ablative techniques to remove the uvula and a significant amount of soft palate tissue. Over the years, these procedures were associated with a high incidence of unfavorable postoperative complications and morbidities [13][14][15][16]. In the short and long term, the most typical problems reported in these patients were dysphagia, rhinolalia, velopharyngeal insufficiency and nasopharyngeal regurgitation, phlegm in throat, and abnormal scarring with velopharyngeal stenosis [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect to keep in mind is postoperative pain, especially during swallowing [12][13][14]. These complications were often reported for UPPP and laser-assisted uvulopalatoplasty (LAUP) where major palate resections were performed [15,16]. On the other hand, lateral pharyngoplasty techniques would seem to have a lower incidence of these postoperative complications [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Palate procedures such as UPPP and expansion sphincteroplasty have been demonstrated to increase hyoid movement time, increase duration of food stasis in the hypopharynx, and decrease pharyngeal constriction time. 5 Patients who underwent transoral robotic tongue base reduction surgery for OSA have exhibited findings of vallecular residue and early spillage, presumably from postoperative changes leading to decreased base of tongue sensitivity from neural damage as well as postoperative scarring. Postoperative dysphagia can present both in the immediate postoperative period and in late stage follow-up.…”
Section: Introductionmentioning
confidence: 99%